Pregnancy with Hypothyroid Secondary to Treatment of Thyroid Carcinoma: A Case Report - Claudio Udjaja; M. Besari Adi Pramono (Diponegoro International Medical Journal, 2021)
Background: Thyroid malignancy is one of the most common malignancies in women of reproductive age. One of the normal physiological change in pregnancy is an increase in total maternal thyroid levels. According to 2015 DATIN information, the prevalence of hypothyroidism in women of reproductive age was 2.2%. Method of delivery in patients with thyroid disorders are mostly by cesarean section due to complications of the mother and/or fetus. Fetal outcome usually associated with low birth weight and poor APGAR Score.Objective : Reporting a case of pregnancy with hypothyroidism secondary to thyroid carcinoma treatmentCase: A 37-year-old woman Gravida 3 Parity 2 Abortion 0 with 18 weeks pregnancy after thyroid ablation treatment with a history of Papillary Thyroid Carcinoma – Follicular Variant, following a complete thyroidectomy in August 2016. The patient was given 6-dose ablation therapy, the last therapy was performed in April 2019. On clinical examination, the patient have no sign and symptoms suggesting hypothyroidism. On laboratory examination, the thyroid stimulating hormone (TSH) level was increased. Levothyroxine dosage was adjusted until the patient in euthyroid status in the early 3rd trimester of pregnancy until the delivery period. The fetal examination suggests that the Bio-Physical Profile was normal according to gestational age. The patient underwent vaginal delivery following 38 weeks of gestation with good maternal outcomes and low birth weight neonatal outcomes, no thyroid nodules, and slightly increased thyroid function.Conclusion : Management of counselling about preconception, contraception, and initial screening of patients with a history of thyroid carcinoma are the initial steps to help a better outcome in pregnancies with thyroid disorders.